Letter to the Editor concerning “Impact of preoperative mental health disorders on postoperative outcomes in patients with adolescent idiopathic scoliosis undergoing surgery” by Vallee EK, et al. (Spine Deformity [2026]: doi:10.1007/s43390-026–01288-z) - Kishankumar Mahida; Snehal Rajendra Jagtap (Spine Deformity, 2026)
Background Extended-wear infusion sets (E-iS) allowing up to 7 days of catheter use have recently become available. Real-world evidence of contemporary automated insulin delivery (AID) systems using E-iS remains limited. Method A prospective non-randomized single-arm real-world study in adults with type 1 diabetes using the MiniMed-780G AID system who transitioned from conventional 3-day infusion sets to E-iS was conducted. Clinical variables, device settings, adverse events, and patient-reported outcomes were assessed at baseline, 3 and 6 months. Results 65 participants were included, 58 completed 6 months of follow-up.Mean catheter wear time increased from 3.6 ± 1.1 to 6.1 ± 2.3 days,(p < 0.001), and reservoir change interval increased from 3.5 ± 1.0 to 5.2 ± 2.3 days,(p < 0.001). Glycemic control remained overall stable, although small changes were observed in some CGM metrics (Time in range-TIR: 80.0 ± 7.1% to 78.0 ± 10.0%, p = 0.014) and slight increases in time above range, while hypoglycemia exposure remained unchanged. HbA1c decreased from 6.8 ± 0.5% to 6.4 ± 1.0%, (p = 0.03). Total daily insulin dose did not change, but insulin use related to infusion set management decreased significantly. Pain at cannula insertion improved from 2.1 ± 1.5 to 1.2 ± 1.1,(p < 0.001), and treatment satisfaction increased from 8.2 ± 1.9 to 9.0 ± 1.2,(p = 0.012). No episodes of severe hypoglycemia or diabetic ketoacidosis occurred. Cannula wear duration was strongly correlated with reservoir change interval (r = 0.712, p < 0.001). At 6 months, 92.3% of participants continued using the E-iS, with 48.3% maintaining the full 7-day wear duration. Conclusions In real-world use with an AID system, the E-iS significantly prolonged catheter wear duration and reservoir change intervals while remaining safe and well tolerated. It was associated with high satisfaction and stable glycemic outcomes, supporting E-iS as a practical strategy to reduce the burden of infusion set changes in routine clinical practice.